Causal association of immune cells and endometriosis: a Mendelian randomization study - Fang, Xingyi; Deng, Qinghua; Yang, Haili; Yan, Zhaohua; Peng, Zhen; Zhao, Yuheng; Liao, Tantan; Tu, Ziying; Liu, Jia; Liu, Li; Zou, Lin; He, Honghua (Frontiers in Endocrinology, 2024)
Objective:To investigate the causal effect of immune cells on endometriosis (EMS), we performed a Mendelian randomisation analysis.Methods: Mendelian randomisation (MR) uses genetic variants as instrumental variables to investigate the causal effects of exposures on outcomes in observational data. In this study, we conducted a thorough two-sample MR analysis to investigate the causal relationship between 731 immune cells and endometriosis.We used complementary Mendelian randomisation (MR) methods, including weighted median estimator (WME) and inverse variance weighted (IVW), and performed sensitivity analyses to assess the robustness of our results.Results: Four immune phenotypes have been found to be significantly associated with the